Therapie schwerer COVID-19-Verläufe in der Intensivmedizin - Busch, M. (Gastroenterologe, 2020)
The pandemic triggered by coronavirus disease 2019 (COVID-19) has put intensive care medicine into the focus of public attention. The mortality of patients with the disease escalates, particularly at the moment when the treatment possibilities of intensive medical care end. In the routine intensive medical care practice, the challenges due to the special features of infections with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its treatment become obvious. These occur in the development and treatment of respiratory and multiorgan failure as well as the severe inflammatory syndrome. For these severe courses there is still only little evidence available as to which interventions are the most effective. In addition to the knowledge that can be gained from the rapid performance of clinical trials, the treatment is therefore based on analogies to other syndromes, such as sepsis and macrophage activation syndrome.